P299 The Role Of A Multidisciplinary Respiratory Hub In Improving Post-discharge Follow Up Of Patients Receiving Acute Non-invasive Ventilation (niv). (10th November 2014) - Rauf, F; Oakes, A; Khan, Y; Stuart, T; Chakraborty, B; Turner, AM; Mukherjee, R
Abstract : Introduction: Post-discharge follow up rate is a national audit metric for acute NIV services in the UK [Davies M. Adult NIV Audit report. BTS Reports 2012. 4 (3): 9–10.]. Appropriate respiratory follow up reduces the number of re-admissions [Turner AM et al . Prim Care Respir J 2013; 22 (1):72–78.] In order to improve post-discharge follow ups, a rapid access one-stop multidisciplinary respiratory outpatient Hub was created at our 709-bedded acute hospital in October 2011. Methods: From the acute NIV database maintained continuously since 2004, we analysed the proportion of discharges that were offered respiratory follow up within 6 months of discharge after Acute NIV during the calendar year 2009 (pre-Hub) and first 6 months of 2013 (post-Hub). Chi-squared test was performed for statistical significance of the observed differences. Results: The proportion of unique discharges offered a follow up appointment at the time of discharge improved from 57% (62/107) pre-Hub to 80% (36/45) post-Hub: p = 0.009. The proportion of patients attending follow-up appointments increased from 40% (42/107) pre-Hub to 58% (26/45) post-Hub: p = 0.036, confirming a statistically significant improvement. The number of acute NIV re-admissions dropped between 2009 and 2013 but expectedly not statistically significant, as only 6 months' data from the post-Hub period was analysed against 12 months of data from the pre-Hub period. Conclusions: The increase in the number of patients attending post-discharge NIV follow up correlates with the direct increase in the number being offered follow up, an improvement most obviously measuring the impact of the multidisciplinary 'Hub'. The Hub would also be the most plausible explanation for the drop in acute NIV re-admissions between the 2 periods, not the least because apart from a 'routine' follow-up, it supports community teams and provides an alternative to ambulance calls to people with complex respiratory needs in a responsive fashion. Further longitudinal evaluation of the Multidisciplinary Hub is necessary to fully understand its impact on the quality and safety of complex respiratory care.